Mādhyamika Śūnyatā: A Reappraisal of Mādhyamika Philosophical Enterprise with Special Reference to Nāgārjuna and Candrakīrti - Potter, Karl (Journal of Dharma, 2003)
G. C. Nayak, Mādhyamika Śūnyatā: A Reappraisal of Mādhyamika Philosophical Enterprise with Special Reference to Nāgārjuna and Candrakīrti, New Delhi: Indian Council of Philosophical Research, pages xi + 93.